Human capital cost and investment policy. Issue 3 (26th July 2021) - Ji, Shuangshuang; King, Tao‐Hsien Dolly; Li, Xinxin
Abstract: In this paper, we examine the link between human capital cost and investment policy. We find a significantly positive relationship between investment risk and the cost of human capital measured by average employee pay, especially when employees have strong bargaining power. We further investigate various channels through which investment risk influences human capital cost and find strong empirical support that these channels are important drivers. Our results suggest that a higher human capital cost associated with an increase in investment risk discourages firms from making valuable but risky investments in the future, leading to a potential problem of underinvestment.